PENGGUNAAN MODEL NHT DALAM MEMBENTUK PERCAYA DIRI PELAJARAN PPKN XI IPS MAN 2 PONTIANAK - Ira Santika, Sulistyarini; Sulistyarini Sulistyarini; Bambang Budi Utomo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The study aims to describe the planning, implementation, the NHT (Numbered Head Together) model assesment in developing learners'confidence on PPKn subject in XI IPS 2 class MAN 2 Pontianak. This type of research is qualitative research descriptive method. The subject of this research are 38 students from XI IPS 2 class. Data collection techniques are observation, interviews, and documentation. The planning of the study was decently planned by the teacher in RPP using NHT model and the RPP which the teacher has made based on the indicator from component and system of 2013 curriculum RPP. On the making of RPP, the teacher has design learning activity that could build learners confidence. The execution of the learning model that teacher do in a class according to the RPP that teacher has created by set up the NHT model. The evaluations that teacher use are attitude, knowledge, and skill assessment. The aspect of judging that relating to confidence are assessment of attitudes and skills, because it contains confidence indicator. The average value of the students confidence at the first meeting is 4,81, and at the second meeting is 5,23 from 6 indicators with good criteria. So, it can be concluded that NHT cooperative learning model could build learners confidence on PPKn subject in XI IPS 2 class MAN 2 Pontianak. Keywords : Confidence, NHT (Numbered Head Together) Model, PPKn